Firefighter Turnout Gear and Peri-Governmental Influences - Kira Mok; Gabriel Wasserman; Phil Brown; Alissa Cordner (NEW SOLUTIONS: A Journal of Environmental and Occupational Health Policy, 2026)
How do non-governmental standards matter for occupational and environmental health and safety? Internationally recognized standards specify requirements for structural firefighter personal protective equipment (PPE), but concerns have emerged about hazardous chemicals and firefighters’ potential exposures. In this paper, we draw on the case of the National Fire Protection Association's standards for firefighter PPE to develop the concept of peri-governance , work done by non-governmental actors or organizations that exerts governance force through various mechanisms, including government entities. We conducted qualitative interviews with firefighters, industry representatives, activists, and other experts to identify firefighter and union concerns related to the development of PPE standards, and advocacy related to those concerns. We find that peri-governmental standards can exert essentially binding influence over sectors of society through four mechanisms: formal regulatory and legal requirements, fear of legal liability, insurance requirements, and universal uptake by relevant users. Peri-governance raises specific concerns about transparency, fairness, and public–private interactions, making the concept useful in examining other standards and governance more broadly.